EFEKTIVITAS PROMOSI MELALUI MEDIA SOSIAL DALAM MENARIK MINAT CALON MAHASISWA BARU FAKULTAS AGAMA ISLAM UNIVERSITAS MUHAMMADIYAH METRO - muhammad fikri; Iswati; Kuliyatun (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
Sosial media is an online media, with users who can easily create, follow, find out about someone's activities and even promote via blogs. With sosial media, people now don't have to communicate directly without thinking about space or time. This research aims to determine the effectiveness of promoting the Faculty of Islamic Religion through sosial media and to determine which sosial media can be said to be effective in promoting the Faculty of Islamic Religion to prospective new students. This research uses quantitative research methods by collecting data through distributing Likert scale questionnaires, interviews and observations. The research population was all 530 students of the Faculty of Islamic Religion, Muhammdiyah Metro University from 2019 to 2022, and the sample taken was 84 students. The results of this research are based on the test carried out, namely the Simple Linear Regression Test, which has a significance value (Sig) of variable Promotional means as variable X are said to be effective in attracting new students because the significance value is less than 0.05. and for the T Test, the calculated t_value for Sosial Media as a Promotional Means is 3,869. at the degrees of freedom (df) = N – 2 = 84 – 2 = 82, the r_table is found to be 0.215, so it can be concluded that the value of t_count > t_tabel (3.869 > 0.215) which means that there is an influence of Sosial Media as a Promotional Means on the Interest of Prospective Students.